Produksi Gula Pereduksi dari Depolimerisasi Pati Singkong Melalui Proses Pelarutan disertai Pemanasan dan Hidrotermal - Febriyati Puspasari; Yoga Asmara; Prida Novarita Trisanti; Sumarno . (Seminar Nasional Teknik Kimia Kejuangan, 2017)
In cassava, the major component are starch (60%). This component can be converted into a high valueproduct, such a reducing sugar and oligosaccharides. Starch conversion can be done by de-polymerizationusing a hydrothermal process. The effect of reaction time in hydrothermal process in reducing sugarproduction was studied in this research. Cassava starch suspension (1:20 (w/v)) was pre-mixing with heatingat 60°C and 45 minutes. Then proceed with the hydrothermal process at 100°C and 100 bar in variousreaction time (15-120 minutes). The solid product were analyzed using Scanning Electron Microscopy(SEM), X-Ray Diffraction (XRD), and Anthrone analysis (starch). And liquid products were analyzed by DNSanalysis to calculate concentration of reducing sugars. From SEM analysis showed hydrothermal processwas attacked the garnules surface deeply and also the inner grannules parts. And concentration of reducingsugars was increase by increasing hydrothermal time.